Combined screening for breast and gynecological cancers using mobile clinics: The barretos experience (Brazil) - Filho, Adhemar Longatto. [UNESP]; Silva, Thiago Buosi.; Rodrigues, Silvana; Haikel, Raphael Luiz. (Springer Nature, 2013)
A mobile clinic is an effective method for providing cancer screening services for women and is particularly suited for women residing in remote locations with limited access to health care. The Barretos experience of providing such services to screen for breast and gynecological cancers is presented in this chapter.